DEVELOPMENT OF E - ACCOUNTING MODULE TO IMPROVE STUDENT'S LEARNING ACHIEVEMENT - Dirmansah Dirmansah; Bambang Sahono (DIADIK, 2019)
This research  aims to improvetheLearning Achievement ofeconomic subjects of the XIIIP SstudentsinSMANegeri1Gumay TalangLahat   throughthe developmentof Accounting  E-Module withthe subjectof the researchare two economic techersand  Studentsof XIIIPS are 30 students,  Studentsof  XIIIPS2 are 30 students  as the experimental class, students of   XIIIPS3  are 30 students asthe controlclass.The objectof  the research  is  theE-Module Accounting.  The result sof the data analysis  sho wthat:a)ThedevelopedE-ModuleofAccounting isappropriate toimprove student achievementin economic subjectsinthe XII grade social studiesat SMA Negeri1Gumay TalangLahat,b)TheE-Moduleof Accountingdeveloped  is  ateaching material    very effectivewayto  improve student achievement in class XIIIPSat GumayTalang Lahat SeniorHigh School